Pengaruh Strategi Pembelajaran dan Kecerdasan Interpersonal terhadap Hasil Belajar PKn Siswa SMP - -, Sunanto (JTP - Jurnal Teknologi Pendidikan, 2015)
The research was aimed to get information about learning strategies based on interpersonal intelligence on civics learning outcomes. The research was conducted on Au- gust until October 2012, at SMP Negeri 10 Bandar Lampung. The researh method used ex- perimental with treatment design by level 2 x 2. The results of research shows: (1) students’ civics learning outcomes who learned by using cooperative learning strategy are higher than those who learned by self – study learning strategy; (2) there is interaction effect be- tween learning strategies and interpersonal intelligence on civics learning outcomes; (3) students’ civics learning outcomes who have high interpersonal intelligence taught coop- erative learning strategy are higher than taught self-study learning strategy.